Institutional Strengthening in Supporting Ecotourism Development in the Branca Area Tourist Area, Dili-Timor Leste - Rideng, I Wayan; Mahendrawati, Ni Luh Made; Setyawati, Ni Komang Arini; Marta, I Dewa Gd Mahardika; Reiro, Leonito; Manuel, Julio (PT FORMOSA CENDEKIA GLOBAL, 2024)
The community service program aimed to strengthen institutional capacity in supporting the development of ecotourism in the Area Branca, Dili, Timor Leste. This research focused on assessing community participation and collaboration among stakeholders, including local government and businesses, to enhance tourism management. Using a qualitative methodology, the study employed observations and focus group discussions conducted between June and August 2024. The findings indicate limited community involvement and weak institutional frameworks as significant barriers to tourism development. Strengthening local institutions and fostering partnerships with external stakeholders were proposed as strategic solutions to enhance tourism management. The results imply potential long-term benefits for local economic growth and sustainable tourism development.